2018
DOI: 10.1002/ecs2.2022
|View full text |Cite
|
Sign up to set email alerts
|

Can sugar maple establish into the boreal forest? Insights from seedlings under various canopies in southern Quebec

Abstract: Abstract. Understanding tree recruitment dynamics in various growth environments is essential for a better assessment of tree species' adaptive capacity to climate change. We investigated the microsite factors influencing survival, growth, and foliar nutrition of natural and planted sugar maple seedlings (Acer saccharum) along a gradient of tree species that reflect the change in composition from temperate hardwoods to boreal forests of eastern Canada. We specifically tested whether the increasing abundance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…stands and maple-beech stands, thus suggesting a greater effect of phenols than other soil properties. However, the levels of phenolic compounds measured in 2013 were in the same range as those observed in conifer-dominated stands with maple regeneration [36]. In addition, these stands had a mean canopy openness and light availability of 29% and 12 mol·m 2 ·day −1 , respectively.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…stands and maple-beech stands, thus suggesting a greater effect of phenols than other soil properties. However, the levels of phenolic compounds measured in 2013 were in the same range as those observed in conifer-dominated stands with maple regeneration [36]. In addition, these stands had a mean canopy openness and light availability of 29% and 12 mol·m 2 ·day −1 , respectively.…”
Section: Discussionsupporting
confidence: 53%
“…It is possible that the rapid change in growing conditions during transplantation may have caused a stress that led to the high mortality. Light availability under the deciduous stands at the SBL (below 22% of canopy openness, Table 2) is a potential candidate for creating the high mortality because the survival rate of the same maple seedlings planted under mixedwood forests at the SBL with similar soil conditions but with a canopy openness of 30% was, on average, 83% [36]. A potential alternative explanation relates to below-ground fungal pathogens, not completely controlled in this study, and which were shown to be density-dependant and responsible for high mortality in maple stands [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary boreal type of substrate, needle cover, was particularly efficient at inhibiting recruitment of temperate tree species, in particular for Acer species ( f = 0.115). Typically, boreal forest substrates are characterized as being thick, acidic and drier when compared within other forest floors (Collin et al, ). The acidification of soils under conifer stands is a general phenomenon (Cole, ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, novel edaphic effects could arise, where the absence of key symbiotic microbial and fungal communities and/or nutrients (e.g. calcium and magnesium) could impact seedling emergence and survival (Collin, Kembel, Messier, & Bélanger, ; Lafleur, Paré, Munson, & Bergeron, ). Furthermore, as microclimate (i.e.…”
Section: Introductionmentioning
confidence: 99%